Assays for hyaluronidases and heparanase using nonreducing end fluorophore-labeled hyaluronan and heparan sulfate proteoglycan. (17th July 2021) - Wu, Zhengliang L; Ertelt, James M
Abstract: Glycosaminoglycans (GAGs), such as hyaluronan (HA) and heparan sulfate (HS), are a large group of polysaccharides found in the extracellular matrix and on the cell surface. The turnover of these molecules is controlled by de novo synthesis and catabolism through specific endoglycosidases, which are the keys to our understanding of the homeostasis of GAGs and could hold opportunities for therapeutic intervention. Herein, we describe assays for endoglycosidases using nonreducing end fluorophore-labeled GAGs, in which GAGs were labeled via incorporation of GlcNAz by specific synthases and cycloaddition of alkyne fluorophores and then digested with corresponding endoglycosidases. Assays of various HA-specific hyaluronidases (HYALs), including PH-20 or SPAM1, and HS-specific heparanase (HPSE) are presented. We demonstrated the distinctive pH profiles, substrate specificities and specific activities of these enzymes and provided evidence that both HYAL3 and HYAL4 are authentic hyaluronidases. In addition, while all HYALs are active on high-molecular-weight HA, they are active on low-molecular-weight HA. Subsequently, we defined a new way of measuring the activities of HYALs. Our results indicate that the activities of HYALs must be under strict pH regulation. Our quantitative methods of measuring the activity GAG endoglycosidases could bring the opportunity of designing novel therapeutics by targeting these important enzymes.